Spark of the everflame - Cole, Penn (Cole, Penn. Kindred's curse saga, 2024)
"In a mortal world colonized by the gods and ruled over by their cruel, magical offspring called the Descended, Diem Bellator yearns to escape her poor village. Her mother's sudden disappearance--and the discovery of a dangerous secret about her past--offer Diem an unexpected opportunity to enter the dark world of Descended royalty and unlock a web of mysteries left behind by her mother. With the dying King's handsome yet enigmatic heir watching her every move and a ruthless rebel alliance recruiting her to join the growing civil war, Diem must navigate the unwritten rules of love, power, and politics in order to save her family--and all of mortalkind"--